2019
DOI: 10.1542/peds.2018-0902
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intubation Practice and Outcomes: An International Registry Study

Abstract: for the NEAR4NEOS Investigators BACKGROUND AND OBJECTIVES: Neonatal tracheal intubation is a critical but potentially dangerous procedure. We sought to characterize intubation practice and outcomes in the NICU and delivery room (DR) settings and to identify potentially modifiable factors to improve neonatal intubation safety. METHODS:We developed the National Emergency Airway Registry for Neonates and collected standardized data for patients, providers, practices, and outcomes of neonatal intubation. Safety ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
216
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(235 citation statements)
references
References 32 publications
13
216
4
2
Order By: Relevance
“…While the definition of adverse TIAEs does not include hypoxemia, these are often reported together. Current evidence suggests 1. adverse TIAEs and hypoxemia are common in airway management in the pediatric ICUs, Emergency Department, and neonatal ICUs, 2. patient, clinician, and practice factors are associated with the occurrence of these adverse events, and 3. interdisciplinary quality improvement has helped reduce these events . Pediatric anesthesiologists can partner with nonanesthesiologists to improve the safety of airway management in these clinical locations.…”
Section: Airway Management In the Pediatric Icu Emergency Departmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While the definition of adverse TIAEs does not include hypoxemia, these are often reported together. Current evidence suggests 1. adverse TIAEs and hypoxemia are common in airway management in the pediatric ICUs, Emergency Department, and neonatal ICUs, 2. patient, clinician, and practice factors are associated with the occurrence of these adverse events, and 3. interdisciplinary quality improvement has helped reduce these events . Pediatric anesthesiologists can partner with nonanesthesiologists to improve the safety of airway management in these clinical locations.…”
Section: Airway Management In the Pediatric Icu Emergency Departmentmentioning
confidence: 99%
“…In neonatal ICUs (NICU) and the delivery room (DR), first‐attempt success was 49% in NICU, 46% in the DR, and the course success was 96% in NICU and 95% in DR . Tracheal intubation was associated with adverse TIAEs in 18% (NICU) and 17% (DR).…”
Section: Airway Management In the Pediatric Icu Emergency Departmentmentioning
confidence: 99%
“…This practice is an essential ethical requirement and best practice, according to the available scientific evidence. However, premedication practices for neonatal endotracheal intubation differ widely and many infants are still being intubated without any analgesia or sedation . The reasons why many neonatologists do not use appropriate premedication have been inadequately evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Second, neonatologists may have been reluctant to change practices they feel work well, despite clinical evidence. This area is only just being researched and a study of neonatologists' performance during endotracheal intubations reported a low success rate of 49% at the first attempt and adverse events in up to 50% of intubations . Furthermore, it has been shown that premedication, especially neuromuscular blocking agents, improves success rates and patient safety .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation